The evolution of Indonesia participation in global value chains. (Metro Manila, Philippines Asian Development Bank, 2019)
The evolving role of Indonesia in GVCs and its exports have impacts on economic performance. However, in a highly globalized environment, the fragmentation of production processes across geographical borders calls for a reevaluation of countries contributions to global production. The report draws on recent empirical and theoretical frameworks in GVC analysis and multiregional input output tables compiled by the Asian Development Bank.
Keywords: Economic development; Electronic books